The mannose receptor in macrophage biology - Gazi, Umut (2010)
The Mannose receptor (MR) is a type I membrane molecule involved in both haemostasis and pathogen recognition. Its extracellular domains have broad ligand specificities: the cysteine-rich (CR) domain is involved in sulphated sugar binding, the C-type lectin-like domains (CTLDs) are responsible for the detection of sugars terminated in mannose, fucose or N-acetylglucosamine, and the fibronectin-type II (FNII) domain mediates collagen binding. Its recently discovered collagen binding ability raised the question of MR facilitating cellular adhesion which would then influence its function as an endocytic receptor in collagen-rich mammalian tissues. For this purpose, the level of MR-mediated endocytosis, and MR expression was analyzed by using bone-marrow-derived macrophages (BM-MΦ) plated on extracellular matrix (ECM) proteins including fibronectin (not a MR ligand), collagen type I or IV (MR-ligands). The results showed no difference in the level of MR-mediated endocytosis and MR expression at both mRNA and protein levels upon MΦ adhesion to collagen. This suggests that MR interaction with collagen may simply be crucial for tissue remodelling and wound healing, rather than adhesion. MR is also expressed in a soluble form (sMR) which is comprised of the extracellular region of intact cell-associated MR (cMR). Even though its precise role is not yet clear, enhanced sMR production was previously shown to help Pneumocystis carinii to evade M phagocytosis by forming a protective coat around the organism. In this work, the mechanism responsible for the fungi-induced MR-shedding was studied by treating MΦ with fungal particles in the presence and the absence of a wide-range of inhibitors. After treatment in serum-free conditions, the cell lysate and cell culture supernatants were analyzed by western blot, for cMR and sMR expression respectively. It was shown that fungi species other than P. carinii can also trigger sMR production, and that this effect mainly takes place through -glucan recognition. Using bio-active particulate -glucan, it was also demonstrated that MR cleavage upon -glucan recognition requires dectin-1-mediated signalling involving Syk, PI3K, and, partially, Raf-1 and that is mediated by a non-secreted metalloproteinase. Dectin-1-mediated MR-shedding may partially explain the contradictive data on the involvement of cMR in the development of immunity against fungi, as well as other pathogens recognised by dectin-1. The ability of pathogens to evade or activate the immune response may depend on the balance between sMR and cMR expression levels.